2010
DOI: 10.1080/01609510903437383
|View full text |Cite
|
Sign up to set email alerts
|

Family Support and Empowerment: Post Autism Diagnosis Support Group for Parents

Abstract: Receiving a diagnosis of an autism spectrum disorder often elicits strong emotional reactions from parents of the diagnosed child. Follow-up services and continued support for these families is a necessary component to help families adapt and meet their and their children's needs. This pilot study measured the effects of a six-session, co-facilitated, support group on the advocacy skills and self-efficacy of parents coping with a child's diagnosis. Statistically significant increases in the average mean scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 15 publications
(17 reference statements)
3
52
0
5
Order By: Relevance
“…Graduate students in social work (MSWs) and early childhood special education (ECSE) were paired as cofacilitators. As previously reported, these c-facilitated groups were found to increase feelings of empowerment for parents (Banach, Iudice, Conway, & Couse, 2010). Findings also indicated that providing this service offered a good opportunity for MSW and ESCE graduate students to improve their skills in interdisciplinary coleadership, communication, and developing a trusting relationship with the family and school (Blue-Banning, Summers, Frankland, Nelson, & Beegle, 2004).…”
Section: Introductionsupporting
confidence: 53%
“…Graduate students in social work (MSWs) and early childhood special education (ECSE) were paired as cofacilitators. As previously reported, these c-facilitated groups were found to increase feelings of empowerment for parents (Banach, Iudice, Conway, & Couse, 2010). Findings also indicated that providing this service offered a good opportunity for MSW and ESCE graduate students to improve their skills in interdisciplinary coleadership, communication, and developing a trusting relationship with the family and school (Blue-Banning, Summers, Frankland, Nelson, & Beegle, 2004).…”
Section: Introductionsupporting
confidence: 53%
“…There is evidence that social support might moderate the severity of symptoms exhibited by the child with an ASD and might be related to adaptive coping and adjustment of siblings (Banach et al 2010;Hastings 2003b;Law et al 2001;Stoneman 2005). Many non-profit organizations provide support group services for families who have a child with autism, such as the Autism Society of America or the ARC of the United States at state and local levels.…”
Section: Support Groupmentioning
confidence: 97%
“…Parent support groups should involve meeting other parents of children with similar conditions. Such meetings offer parents the knowledge, understanding, and acceptance they seek (Banach et al 2010). Through programs like a family support group or a parent-to-parent group, families have a place to share their joys and concerns, learn lessons to better support their child's needs, exchange information, and generally support each other.…”
Section: Support Groupmentioning
confidence: 98%
“…For parents of children with disabilities, a growing body of evidence documents that parent-to-parent support groups provide positive assistance in managing the needs of parents and families as they seek service for their child (Banach, Iudice, Conway, & Couse, 2010;McHugh, Bailey, Shilling, & Morris, 2013;Olin et al, 2014;Shilling et al, 2013;Wisdom et al, 2013;Wright & Wooden, 2013 provides relational well-being, a sense of belonging and adaptational help, which is not provided by clinical or medical providers. Supported parents are better able to care for their children, and parent-to-parent support provides parents with the skills to help their children in goal setting, speech and language development and participation in schools and community (Henderson, Johnson, & Moodie, 2014).…”
Section: Parent-to-parent Supportmentioning
confidence: 99%